The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0864-34662010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Tendencia de la mortalidad por cáncer en Argentina, Cuba y Uruguay en un período de 15 años

Abstract: Introduction Cancer is the second cause of death in Argentina, Cuba and Uruguay during the last decade, cancer mortality has shown a decrease trend in developed countries. Objective To describe mortality trends over time by cancer site in Argentina, Cuba and Uruguay during 1990-2005. Methods For each cancer site, country and gender, age-group specific and standardised (overall) rates were calculated by direct method (using the world standard population). The jointpoint regression analysis was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Int are shown the tumors with more than one stage of metastasis (given the nearest integer, one stage or a step is the first metastasis in a secondary site, and two steps is the second metastasis in a tertiary site). Bladder and Thyroid have a higher number of steps, Lung and Kidney have the maximal steps around two, this coincides with the main trend of mortality in males due to these tumors [12], [21].…”
Section: J= N a O Isupporting
confidence: 59%
See 2 more Smart Citations
“…Int are shown the tumors with more than one stage of metastasis (given the nearest integer, one stage or a step is the first metastasis in a secondary site, and two steps is the second metastasis in a tertiary site). Bladder and Thyroid have a higher number of steps, Lung and Kidney have the maximal steps around two, this coincides with the main trend of mortality in males due to these tumors [12], [21].…”
Section: J= N a O Isupporting
confidence: 59%
“…1, it can be seen that the Lung is the principal link. Although the principal primary sites are Prostate, Colon or Rectum, Lung tumor is the most common but usually comes from some primary site, being the principal secondary site ( [12], [13]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer is the most common cancer among Hispanic and Latino men in the United States, accounting for more than 17,600 new cases and 2400 deaths per year 1 . It is also one of the leading causes of cancer death among men in Latin American countries 2–4 . However, there is a lack of representation of Hispanic and Latino men in genomic studies of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is also one of the leading causes of cancer death among men in Latin American countries. [2][3][4] However, there is a lack of representation of Hispanic and Latino men in genomic studies of prostate cancer. For example, a review of patient data from The Cancer Genome Atlas Program (TCGA) database showed that only 3% of patients self-reported as Hispanic or Latino.…”
Section: Introductionmentioning
confidence: 99%